DEVELOPMENT OF THE COMPOSITION OF THICKENING COMPOSITIONS FOR PADDING FABRICS BASED ON MIXED FIBERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The viscosity of the developed composition was studied depending on the concentration of the components and it was found that an increase in the concentration of PVA and AE promotes an increase in the viscosity of the system. Because of this, the developed polymer composition becomes stable during long-term storage, which is an important factor from a technological point of view. The change in thermodynamic parameters during the formation of thickening compositions was studied.